Optimization of Enzymatic Hydrolysis Condition for Producing Black Gram Bean (Vigna mungo) Hydrolysate with High Antioxidant Activity - Bumrungsart, Naruemol; Duangmal, Kiattisak (Food and Applied Bioscience Journal, 2019)
Black gram bean (Vigna mungo) hydrolysate was produced using commercial enzyme, Flavourzyme® to break down the peptide bonds. Hydrolysis conditions i.e. enzyme concentration of 1–7% (by dried weight of steamed bean) and hydrolysis time of 60–1200 min, were optimized for high antioxidant activity hydrolysate using response surface methodology based on central composite rotational design. The effect of hydrolysis conditions on degree of hydrolysis (DH), total phenolic content (TPC), browning and antioxidant activity as DPPH radical scavenging activity and ferric reducing antioxidant power (FRAP) was determined. The results of this study showed that increasing the enzyme concentration and hydrolysis time significantly affected DH as increasing DH influenced amount of free amino groups, released TPC and Maillard reaction products (MRPs); these components affected the antioxidant activity of black gram bean hydrolysate. The optimum hydrolysis condition to reach DH of 75% was 6.09% Flavourzyme® and 360 min of hydrolysis time, giving a predicted value of DPPH radical scavenging activity and FRAP values in the range of 80.47–80.48% and 1.42–1.43 µmol Trolox per gram of black gram beans (d.b.), respectively. The validation was confirmed using percentage error measurement. It was found that the observed values were different from the predict values within a range of 0.54–27.46% error. Thus, the obtained optimized model could be used for predicting desired responses for black gram bean hydrolysate production.